The effect of community of practice in improving the role of clinical instructor in patient safety implementation by prelicensure nursing students - Dyah Wiji Puspita Sari; Hanny Handiyani; Kuntarti Kuntarti; Yuni Sufyanti Arief (PAGEPress Publications, 2023)
Introduction: Patient safety problems caused by students leads to different adverse event, hence clinical instructor plays a role in guiding them in the implementation of patient safety programs. Furthermore, the community of practice is considered to improve the role of clinical instructors in patient safety problems. This study is then conducted to measure the impact of community of practice toward the role of clinical instructors in patient safety problems. Design and methods: This is a pre-experimental design for one group and a pre-post test design without a control group. In addition, the sample includes 36 prelicensure nursing students. Result: The results showed that the score of clinical instructors' role before and after intervention with community of practice implementation was 58 (34-67) and 79.33 with SD of 10,960, respectively, with a significant increase of 24.27. Also, the statistic analysis depicted that the role had a significant effect after implementation, with a p-value of < 0,000. Conclusions: Based on the results, the community of practice had a significant impact in increasing the role of clinical instructors in the implementation of patient safety problems by prelicensure nursing students.